2020
DOI: 10.1016/j.heliyon.2020.e05552
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ knowledge and attitude towards diabetes foot care in Bahir Dar, North West Ethiopia

Abstract: A diabetes foot ulcer is the commonest non-traumatic reason for the amputation of the lower extremities. All adults with diabetes should undergo comprehensive foot evaluation at least annually, but for high-risk individuals with diabetes more frequently by a health care provider and daily by the people themselves. Nurses' knowledge and attitude are fundamental to conduct a diabetes foot risk assessment and provide foot care for known diabetes person. Knowledge and attitude of nurses about the assessment and ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…In South Gondar Zone, there are one comprehensive referral hospital found in Debre Tabor Town and seven district government hospitals found in Addis Zemen, Mekane Eyesus, Andabet, Ebenat, Arb Gebeya, Nefas Mewcha, and Wegeda twons. In addition, there are 98 government health centers, and 76 private clinics in South Gondar Zone [ 22 ]. According to the reports of hospitals in the South Gondar Zone, the average number of monthly visitors during COVID-19 was 13,440.…”
Section: Methodsmentioning
confidence: 99%
“…In South Gondar Zone, there are one comprehensive referral hospital found in Debre Tabor Town and seven district government hospitals found in Addis Zemen, Mekane Eyesus, Andabet, Ebenat, Arb Gebeya, Nefas Mewcha, and Wegeda twons. In addition, there are 98 government health centers, and 76 private clinics in South Gondar Zone [ 22 ]. According to the reports of hospitals in the South Gondar Zone, the average number of monthly visitors during COVID-19 was 13,440.…”
Section: Methodsmentioning
confidence: 99%
“…A Chi-square test was used to investigate the association of knowledge or attitude with socio-demographic characteristics, including age, gender, level of education, history of wound care training, interest in diabetic ulcer care, and the use of the following as sources of knowledge: books, guidelines, research articles or journals, magazines, seminars, and sharing with peers. Variables with P -values less than or equal to 0.2 in the bivariate analysis were then entered into a multivariate logistic regression model [ 17 , 35 ]. To investigate the strength of the association between dependent and independent variables, odds ratios ( OR ) with 95% confidence interval (CI) were determined.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is essential that nurses have sufficient knowledge and positive attitudes [ 15 , 16 ]. Knowledge should be a basis that guides nurses in the management of diabetic foot ulcers to prevent amputation [ 17 , 18 ]. Studies have shown that nurses with good knowledge and attitudes are more inclined to participate in diabetic foot ulcer care [ 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,7,9,10 There is therefore widespread uncertainty about the value and best mode of delivery of DFD education. [11][12][13][14][15][16] The aim of this systematic review and meta-analysis was to assess the effectiveness of DFD-specific educational interventions on a wider range of DFD-related outcomes, including not only foot ulcer risk, but also ulcer healing, infection, amputation, mortality, modifiable risk factors, DFD-knowledge, foot self-care behaviours, healthrelated quality of life (HRQOL), and anxiety and depression. This was achieved through analysis of RCTs that tested any form of DFDfocused educational programme in people with or at risk of DFD.…”
mentioning
confidence: 99%